Physical properties of robusta coffee berries during drying: determination and modelling - Botelho, Fernando Mendes; Correa, Paulo Cesar; Botelho, Sílvia de Carvalho Campos; Elías, Guillermo Asdrúbal Vargas; Almeida, Mayra Darliane Silva Diniz; Oliveira, Gabriel Henrique Horta de (Coffee Science - ISSN 1984-3909, 2016)
The objective of this work was to evaluate the influence of moisture content in physical properties of coffee berries (Coffea canephora) during drying. Ripe coffee berries with initial moisture content of 1.7 (d.b.) were used, dried in an oven with forced air circulation at 40 ° C, until final moisture content of around 0.13 (d.b.) was reached. During the drying process were evaluated angle of repouse, bulk and true density, porosity and shape factors (main characteristic dimensions, equivalent diameter, sphericity, roundness and the surface-area-to-volume ratio) and analyzed by function of moisture content. It was found that moisture content greatly influences the physical properties of the analyzed coffee berries. With the exception of the surface-area-to-volume ratio, all of these properties decreased by reducing the moisture content. It was also observed that the factors tended to stabilize for the moisture content between 0.42 and 0.68 (d.b.).